Poziom sytuacyjnej wrażliwości edukacyjnej uczniów z uszkodzonym słuchem w momencie startu edukacyjnego - Olempska-Wysocka, Magdalena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Situational educational sensitivity is one of the components of the educational sensitivity model, which is the child's vulnerability to the implementation of tasks related to the role of the student. There are situational sensitivity of instrumental processes and situational educational sensitivity of directional processes. The study involved 74 children with hearing impairment in a profound and significant degree, beginning their studies in the first grade in primary school. The research was carried out in the first semester, in central Poland, in integration and special schools. The aim of the research was to determine the situational level of sensitivity of deaf pupils starting school education. The conducted research allows to determine which of the ranges are the best and the least developed, which enables orientation towards the rehabilitation and therapeutic interactions of this group of students.